Таван шалтгааны үр: The result of the five reasons [tibetan: rgyu lnga\ - П., Даваапил; Чү., Гоо (Mongolian Studies, 2023)
While we are watching any performance of singers, musicians and actors, we observe their singing, acting and other performances attentively. We can notice their mispronunciations, poor lilts, unnecessary movement and forgetting the lyrics or words due to embarrassment. If they perform them without any fault, we express our inner enjoyment with the roaring applause. The main reason for this is related to how the performer of the sound and melody expresses their knowledge and skill. If they haven’t gained enough skill and knowledge as they can’t perform as they want to, it is explained in the “Commentary on music treatise” as the concept of “Five reasons”. My purpose of this article is to compare the concept of “Five Reasons” with the knowledge, experience and other advices of singing art teachers.